A method for preparing lactone by oxidation
By using metal-containing multi-stage pore molecular sieve composite materials as catalysts, the problems of low catalyst activity and poor yield selectivity in the existing lactone synthesis methods are solved, and high-efficiency lactone synthesis under mild conditions is achieved and high-value carboxylic acids are produced by-product.
Patent Information
- Application Number
- CN202111424551.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The existing lactone synthesis methods have problems such as low catalyst activity, poor yield and selectivity of caprolactone, and difficult to recover and utilize the catalyst, which is difficult to meet the growth of market demand.
The metal-containing multi-stage pore molecular sieve composite material is used as a catalyst to achieve high conversion of ketones and high selectivity of lactones under mild conditions through B-V oxidation reaction, and at the same time, high-value carboxylic acids are produced by-products.
Achieve high conversion rate and high selectivity under mild conditions, produce high-value products by-products, and have high industrial application value.
Smart Images

Figure CN116178325B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fine chemicals, and in particular, to a method for preparing lactone by oxidation. Background Art
[0002] Lactone is an important organic synthesis intermediate, mainly used for the synthesis of polycaprolactone and copolymerization or blending modification with other esters; lactone can also be used as a strong solvent to dissolve many polymer resins, and has good solubility for some difficult-to-dissolve resins, such as chlorinated polyolefin resins and "ESTANE" polyurethane resins. Among them, polycaprolactone (PCL) is a linear aliphatic polyester obtained by ring-opening polymerization of lactone (ε-CL).
[0003] The synthesis of lactones faces problems such as raw material quality, production safety and product stability, so the synthesis technology is difficult. Currently, only a few foreign companies are producing it, and my country mainly relies on imports.
[0004] Lactones were successfully synthesized in the laboratory as early as the 1930s. At present, the industrial lactone synthesis process is synthesized by ketones through the Baeyer-Villiger reaction: ozone is used to directly oxidize acetaldehyde in ethyl acetate solvent to obtain peracetic acid, and the obtained peracetic acid is further oxidized to ketones to synthesize crude lactones, and the pure product is obtained by vacuum distillation. The key to this process is the preparation of peracetic acid. Since the temperature must be strictly controlled at around 0°C during the direct oxidation of acetaldehyde by oxygen, when the temperature is higher than 20°C, acetaldehyde is oxidized to acetic acid. More importantly, an extremely explosive intermediate product will be generated during the oxidation process. In recent years, with the continuous expansion of the application field of lactones, market demand has also continued to increase, and the development of lactone synthesis technology has received more and more attention. The synthesis methods of lactones reported in the literature currently also include the use of peracid oxidation, low-concentration H2O2, O2 / air, etc. as oxidants to oxidize ketones to synthesize ε-lactones, and biological oxidation methods, but these methods have the following shortcomings: low catalyst activity, poor yield and selectivity of caprolactone, and difficult catalyst recycling. Summary of the invention
[0005] The purpose of the present disclosure is to provide a method for preparing lactones by oxidation. The method uses a metal-containing multi-level porous molecular sieve for BV oxidation reaction, and can obtain a high ketone conversion rate and lactone selectivity under relatively mild conditions, while producing high-value carboxylic acids as by-products, which has high industrial application value.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing lactone by oxidation, characterized in that the method comprises the following steps:
[0007] Under oxygen conditions, a mixed raw material containing ketone compounds, aldehyde compounds and alcohol compounds is brought into contact with a catalyst to perform an oxidation reaction;
[0008] The catalyst is a composite material, which includes an all-silicon molecular sieve and a metal element M dispersed in the crystals of the all-silicon molecular sieve.
[0009] Optionally, the composite material has the following FT-IR characteristics:
[0010] The FT-IR spectrum of the composite material has a wave number of 960 cm -1 The peak intensity is recorded as I1, and the wave number is 800 cm -1 The peak intensity is recorded as I2,
[0011] I0 defined by the following formula (1) is any value between 0.5 and 1.3;
[0012] I0=I1 / I2 Formula (1);
[0013] Preferably, the value of I0 is any value between 0.6 and 1.3.
[0014] Optionally, the ketone compound is selected from one or more of aliphatic ketone compounds having 4 to 10 carbon atoms, aromatic ketone compounds having 8 to 16 carbon atoms, and cycloalkanone compounds having 5 to 10 carbon atoms;
[0015] The aldehyde compound is selected from one or more of isobutylaldehyde, isovaleraldehyde and n-hexanal;
[0016] The alcohol compound is selected from at least one of primary alcohols and secondary alcohols having 4 to 10 carbon atoms;
[0017] The molar ratio of the ketone compound, the aldehyde compound and the alcohol compound is 1:(0.05-1):(0.5-5), preferably 1:(0.05-0.5):(0.5-2).
[0018] Optionally, the conditions of the oxidation reaction include: reaction temperature of 40-100°C, preferably 80-100°C; time of 1-48h, preferably 2-24h; oxygen pressure of 0.1-0.5MPa, preferably 0.1-0.3MPa;
[0019] The weight ratio of the catalyst to the ketone compound is 1:(1-20); preferably 1:(1-10);
[0020] Optionally, the reactor for the oxidation reaction includes any one of a tank reactor, a fixed bed reactor, a moving bed reactor, a suspended bed reactor and a slurry bed reactor.
[0021] Optionally, the all-silicon molecular sieve in the composite material is at least one of MFI structure molecular sieve, MEL structure molecular sieve, BEA structure molecular sieve, MWW structure molecular sieve, two-dimensional hexagonal structure molecular sieve, MOR structure molecular sieve and TUN structure molecular sieve; preferably one or more selected from MFI structure molecular sieve, MEL structure molecular sieve, BEA structure molecular sieve, MCM structure molecular sieve and SBA structure molecular sieve; further preferably one or more selected from MFI structure molecular sieve, MEL structure molecular sieve and BEA structure molecular sieve;
[0022] The metal M is selected from one or more of manganese, iron, cobalt, nickel, palladium, platinum, copper and gold.
[0023] Optionally, in the composite material, the molar ratio of the metal element M to the silicon element is (0.001-0.2):1, preferably (0.001-0.16):1.
[0024] Optionally, the BET specific surface area of the composite material is 400 to 800 m 2 / g, the total pore volume is 0.3-0.65mL / g, the micropore volume is 0.1-0.19mL / g, the mesopore volume is 0.2-0.46mL / g, and the metal element M exists in the form of metal nanoparticles, and the average particle size of the metal nanoparticles is 0.5-9nm.
[0025] Optionally, the catalyst is prepared by a preparation method comprising the following steps:
[0026] S1, mixing a template, a silicon source, water, a metal M precursor, a nitrogen-containing ligand and a silanization agent to obtain a reaction mixture;
[0027] S2. performing hydrothermal crystallization and calcination on the reaction mixture.
[0028] Optionally, in step S1, the molar ratio of silicon source: template: water: metal M element: silanization agent calculated as SiO2 is 1: (0.001~1): (5~100): (0.001~0.2): (0.025~0.4), preferably 1: (0.001~1): (5~100): (0.001~0.16): (0.025~0.3); the molar ratio of nitrogen-containing ligand to metal element M is (0.2~2):1.
[0029] Optionally, step S1 includes:
[0030] a. mixing a template, a silicon source and water to obtain a silicon hydrolysis solution;
[0031] b. adding a nitrogen-containing ligand to an aqueous solution of a metal M precursor, and mixing the mixture to obtain a first mixed material; and mixing the first mixed material with the hydrolyzed silicon solution to obtain a second mixed material;
[0032] c. Adding a silanization agent to the second mixed material, and mixing to obtain the reaction mixture; preferably, the mixing conditions in step c include: stirring at 20 to 80° C. for 0.5 to 2 hours.
[0033] Optionally, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably selected from at least one of organic silicone grease, solid silica gel and white carbon black; further preferably organic silicone grease, the general formula of the organic silicone grease is the structure shown in the following formula (A):
[0034]
[0035] Where R a , R b , R c , R d Each is independently selected from an alkyl group having 1 to 6 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, R a , R b , R c , R d Each is independently selected from a straight-chain alkyl group having 1 to 4 carbon atoms or a branched-chain alkyl group having 3 to 4 carbon atoms; further preferably, the R a , R b , R c , R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl; further preferably, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicone grease.
[0036] Optionally, in step S1, the template is an organic base, preferably at least one selected from quaternary ammonium bases, aliphatic amines and aliphatic alcohol amines; further preferably, the template is at least one selected from quaternary ammonium bases having a structure represented by the following formula (B):
[0037] R1, R2, R3 and R4 are independently selected from an alkyl group having 1 to 4 carbon atoms, preferably a straight-chain alkyl group having 1 to 4 carbon atoms and a branched-chain alkyl group having 3 to 4 carbon atoms, more preferably R1, R2, R3 and R4 are independently selected from at least one of a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, an isobutyl group and a tert-butyl group;
[0038] Further preferably, the molecular sieve of the composite material is an MFI type molecular sieve, and the template is tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide; or
[0039] The molecular sieve of the composite material is a MEL type molecular sieve, and the template agent is tetrabutylammonium hydroxide or a mixture of tetrabutylammonium hydroxide and one or more selected from tetrabutylammonium chloride and tetrabutylammonium bromide; or
[0040] The molecular sieve of the composite material is a BEA type molecular sieve, and the template agent is tetraethylammonium hydroxide or a mixture of tetraethylammonium hydroxide and one or more selected from tetraethylammonium chloride and tetraethylammonium bromide.
[0041] Optionally, in step a, the silicon source is organic silicone grease, and after the template, the organic silicone grease and water are mixed, a hydrolysis and alcohol removal treatment is further performed to obtain a hydrolyzed solution of the silicon;
[0042] The conditions for the hydrolysis and alcohol removal treatment include: stirring and hydrolyzing at 0 to 95° C. for 2 to 10 hours; preferably stirring and hydrolyzing at 50 to 95° C. for 2 to 8 hours.
[0043] Optionally, in step S1, the metal M precursor is one or more of an inorganic metal compound and an organic metal compound; the inorganic metal compound is a water-soluble inorganic salt of metal M; the water-soluble inorganic salt of metal M is selected from one or more of chloride, hydrated chloride, sulfate, hydrated sulfate and nitrate of metal M; the organic metal compound is an organic ligand compound of metal M; preferably, the metal M precursor is a water-soluble inorganic salt of metal M;
[0044] The metal M is selected from one or more of manganese, iron, cobalt, nickel, palladium, platinum, copper and gold;
[0045] Preferably, the metal M precursor is an aqueous solution of a metal M precursor, and the molar ratio of the metal M element to water in the aqueous solution of the metal M precursor is 1:(50-500).
[0046] Optionally, in step S1, the general formula of the silanization agent is R5Si(R6)(R7)R8, wherein R5, R6, R7, and R8 are each independently a halogen, an alkyl group, an alkoxy group, an aromatic group, a thiol group, or an amine group, and at least one of R5, R6, R7, and R8 is an alkyl group, an alkoxy group, an aromatic group, a thiol group, or an amine group; the number of carbon atoms of the alkyl group, the alkoxy group, the thiol group, and the amine group are each independently 1 to 18, and the number of carbon atoms of the aromatic group is 6 to 18;
[0047] Preferably, the silanization agent is selected from one or more of dimethyldichlorosilane, N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, 1,7-dichlorooctylmethyltetrasiloxane, hexadecyltrimethoxysilane, octyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane; further preferably, it is at least one of N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane.
[0048] Optionally, in step S1, the nitrogen-containing ligand is an alkylamine compound containing only an amino group or an amine compound containing other coordination groups, and the other coordination groups include one or more of hydroxyl, carboxyl, carbonyl, and thiol;
[0049] Preferably, the nitrogen-containing ligand is one or more of an alkylamine compound containing only an amino group having a structure shown in the following formula (C), an alcoholamine compound having a structure shown in the following formula (D), and an aminocarboxylic acid compound having a structure shown in the following formula (E):
[0050] R9(NH2) n Formula (C);
[0051] wherein n is 1 or 2; when n is 1, R9 is an alkyl group having 1 to 6 carbon atoms, preferably a linear alkyl group having 1 to 6 carbon atoms and a branched alkyl group having 3 to 6 carbon atoms, and more preferably one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, isopentyl, tert-pentyl and n-hexyl; when n is 2, R9 is an alkylene group having 1 to 6 carbon atoms, preferably a linear alkylene group having 1 to 6 carbon atoms and a branched alkylene group having 3 to 6 carbon atoms, and more preferably one of methylene, ethylene, n-propylene, n-butylene, n-pentylene and n-hexylene;
[0052] (HOR 10 ) m NH (3m) Formula (D);
[0053] Where R 10 is an alkylene group having 1 to 4 carbon atoms and a branched alkylene group having 3 to 4 carbon atoms, preferably one of methylene, ethylene, n-propylene and n-butylene; m is 1, 2 or 3. When m is greater than 1, multiple R 10 Same or different;
[0054] (HOOCR 11 ) x NH (3x)Formula (E);
[0055] Where R 11 is an alkylene group having 1 to 4 carbon atoms and a branched alkylene group having 3 to 4 carbon atoms, preferably one of methylene, ethylene, n-propylene and n-butylene; x is 1, 2 or 3. When x is greater than 1, multiple R 11 Same or different;
[0056] More preferably, the nitrogen-containing ligand is selected from one or more of ethylamine, ethylenediamine, ethanolamine and ethylenediaminetetraacetic acid.
[0057] Optionally, in step S2, the conditions of the hydrothermal crystallization treatment include: under autogenous pressure conditions, the hydrothermal crystallization time is 0.5 to 10 days, and the hydrothermal crystallization temperature is 110 to 200° C.; preferably, the hydrothermal crystallization time is 0.5 to 5 days, and the hydrothermal crystallization temperature is 150 to 200° C.;
[0058] Optionally, the conditions for the calcination treatment include: a calcination temperature of 400 to 900° C. and a calcination time of 1 to 16 hours; preferably, a calcination temperature of 400 to 800° C. and a calcination time of 2 to 8 hours.
[0059] Through the above technical scheme, the present disclosure provides a method for preparing lactone by oxidation, which uses a metal-containing multi-level porous molecular sieve composite material as a catalyst for preparing lactone by oxidation reaction of ketone compounds, and the molecular sieve of the composite material has a large specific surface area, pore volume and macromolecular substrate reaction activity; and the metal oxide nanoparticles have a uniform particle size and are evenly dispersed in the mesoporous channels of the multi-level porous molecular sieve, with a high degree of dispersion, and have high catalytic activity in the aldehyde-alcohol-ketone oxygen co-oxidation reaction. The method of the present disclosure can obtain high conversion rate and lactone selectivity under relatively mild conditions, and at the same time produce high-value carboxylic acids as by-products.
[0060] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0062] Figure 1 This is the infrared (FT-IR) spectrum of the cobalt-containing multi-level pore MFI structure molecular sieve prepared in Example 1;
[0063] Figure 2 The XRD spectrum of the cobalt-containing multi-level pore MFI structure molecular sieve prepared in Example 1;
[0064] Figure 3This is the SEM spectrum of the cobalt-containing multi-level pore MFI structure molecular sieve prepared in Example 1. DETAILED DESCRIPTION
[0065] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0066] The first aspect of the present disclosure provides a method for preparing lactone by oxidation, the method comprising the following steps:
[0067] Under oxygen conditions, a mixed raw material containing ketone compounds, aldehyde compounds and alcohol compounds is brought into contact with a catalyst to perform an oxidation reaction;
[0068] The catalyst is a composite material, which includes an all-silicon molecular sieve and a metal element M dispersed in the crystals of the all-silicon molecular sieve.
[0069] The inventors of the present disclosure unexpectedly discovered that using a composite material of metal nanoparticles and molecular sieves as a catalyst to carry out an oxidation reaction of ketone compounds under the action of the catalyst can effectively increase the oxidation reaction rate, shorten the reaction time, and achieve a high conversion rate of ketones and a high selectivity of lactones under relatively mild conditions, while producing high-value carboxylic acids as by-products.
[0070] In one embodiment, the composite material has the following FT-IR characteristics:
[0071] The FT-IR spectrum of the composite material has a wave number of 960 cm -1 The peak intensity of the highest peak is recorded as I1, and the wave number is 800 cm -1 The peak intensity of the highest peak is recorded as I2,
[0072] I0 defined by the following formula (1) is any value between 0.5 and 1.3;
[0073] I0=I1 / I2 Formula (1);
[0074] The molecular sieve of the composite material has a large specific surface area, pore volume and macromolecular substrate reaction activity; the molecular sieve of the composite material has a multi-level pore structure, and the metal oxide nanoparticles have uniform particle sizes and are evenly dispersed in the mesoporous channels of the multi-level pore molecular sieve; the composite material has high catalytic activity.
[0075] The inventors of the present disclosure surprisingly found in a large number of experimental studies that when a metal precursor, a nitrogen-containing ligand and a silanization agent are introduced into the molecular sieve synthesis process, after the reaction mixture is subjected to hydrothermal crystallization, washing and calcination, the obtained composite material including the all-silicon molecular sieve and the metal M oxide nanoparticles not only has a large specific surface area and pore volume performance, but also the metal oxide nanoparticles have uniform particle size and are evenly dispersed in the molecular sieve crystal (for example, in the molecular sieve mesopores), and may also exist on the surface of the molecular sieve pores; and the inventors also found that the obtained composite material has a 960cm -1 The highest peak intensity (I1) at 800 cm -1 The ratio of the highest peak intensity (I2) at 960 cm-1 to the highest peak intensity (I0) at 960 cm-1 is related to the catalytic performance of the composite material. In particular, when I0 (I0 = I1 / I2) satisfies 0.5 to 1.3, the composite material has good catalytic activity in the co-oxidation reaction of aldol-ketone and can obtain a higher ketone conversion rate and lactone selectivity. It should be understood that in the present disclosure, “960 cm-1” refers to the ratio of the highest peak intensity (I2) at 960 cm-1. -1 "Infrared spectrum 960cm -1 Within a certain range nearby, such as 955-965cm -1 , "800cm -1 "Infrared spectrum 800cm -1 Within a certain range nearby, such as 795-805cm -1 .
[0076] In a preferred embodiment, the value of I0 is any value between 0.6 and 1.3, and the composite material has higher catalytic activity when I0 is within this range.
[0077] In one embodiment, the ketone compound is selected from one or more of aliphatic ketone compounds having 4 to 10 carbon atoms, aromatic ketone compounds having 8 to 16 carbon atoms, and cycloalkanone compounds having 5 to 10 carbon atoms;
[0078] The aldehyde compound is selected from one or more of isobutylaldehyde, isovaleraldehyde and n-hexanal;
[0079] The alcohol compound is selected from at least one of primary alcohols and secondary alcohols having 4 to 10 carbon atoms;
[0080] The molar ratio of the ketone compound, the aldehyde compound and the alcohol compound is 1:(0.05-1):(0.5-5), preferably 1:(0.05-0.5):(0.5-2).
[0081] In one embodiment, the conditions of the oxidation reaction include: reaction temperature of 40-100° C., preferably 80-100° C.; time of 1-48 h, preferably 2-24 h; oxygen pressure of 0.1-0.5 MPa, preferably 0.1-0.3 MPa; weight ratio of the catalyst to the ketone compound of 1:(1-20); preferably 1:(1-10);
[0082] In one embodiment, the reactor for the oxidation reaction includes any one of a tank reactor, a fixed bed reactor, a moving bed reactor, a suspended bed reactor and a slurry bed reactor.
[0083] In one embodiment, the all-silicon molecular sieve in the composite material is one or more of MFI structure molecular sieve (such as S-1), MEL structure molecular sieve (such as S-2), BEA structure molecular sieve (such as Beta), MWW structure molecular sieve (such as MCM-22), two-dimensional hexagonal structure molecular sieve (such as MCM-41, SBA-15), MOR structure molecular sieve (such as MOR), TUN structure molecular sieve (such as TUN) and silicon molecular sieves of other structures (such as ZSM-48, MCM-48); preferably, it is one or more selected from MFI structure molecular sieve, MEL structure molecular sieve, BEA structure molecular sieve, MCM structure molecular sieve and SBA structure molecular sieve; further preferably, it is one or more of MFI structure molecular sieve, MEL structure molecular sieve and BEA structure molecular sieve, such as the silicon molecular sieve is one of S-1, S-2 and Beta; further preferably, it is an MFI structure molecular sieve, such as S-1.
[0084] In one embodiment, the metal M is selected from one or more of manganese, iron, cobalt, nickel, palladium, platinum, copper and gold.
[0085] In one embodiment, the composite material includes silicon element, metal element M and oxygen element, and the molar ratio of the metal element M to the silicon element is (0.001-0.2):1, preferably (0.001-0.16):1.
[0086] In one embodiment, the BET specific surface area of the composite material is 400 to 800 m 2 / g, the total pore volume is 0.3-0.65mL / g, the micropore volume is 0.1-0.19mL / g, the mesopore volume is 0.2-0.46mL / g, the metal M exists in the form of metal nanoparticles, and the average particle size of the metal nanoparticles is 0.5-9nm. The composite material disclosed in the present invention also has a multi-level pore structure, which is conducive to catalyzing reaction substrates of different sizes.
[0087] In one embodiment, the catalyst is prepared by a preparation method comprising the following steps:
[0088] S1, mixing a template, a silicon source, water, a metal M precursor, a nitrogen-containing ligand and a silanization agent to obtain a reaction mixture;
[0089] S2. performing hydrothermal crystallization and calcination on the reaction mixture.
[0090] The present invention introduces a metal precursor, a nitrogen-containing ligand and a silanization agent into the raw materials for the crystallization synthesis of the molecular sieve, which can simultaneously achieve the effects of highly dispersing metal oxide nanoparticles in the molecular sieve crystal and expanding the pores of the molecular sieve support layer, thereby preparing a multi-level porous molecular sieve composite material with highly dispersed metal oxide nanoparticles.
[0091] In the present disclosure, on the one hand, the metal ions in the reaction mixture are complexed with the nitrogen-containing ligands to achieve the effect of dispersing and stabilizing the metal; at the same time, at least one coordination group of the silanization agent can also be complexed with the metal ions to achieve the effect of fixing and dispersing the metal, so that the metal oxide nanoparticles in the molecular sieve pores obtained after hydrothermal crystallization and calcination have high dispersion; on the other hand, the alkyl chain of the silanization agent also ensures the realization of the molecular sieve support layer expansion effect of the synthesized composite material. Thus, a multi-level porous all-silicon molecular sieve composite material with highly dispersed metal nanoparticles is finally prepared.
[0092] In one embodiment, in step S1, the molar ratio of SiO2: template: water: metal M element: silanization agent in the reaction mixture is 1: (0.001-1): (5-100): (0.001-0.2): (0.025-0.4), preferably 1: (0.001-1): (5-100): (0.001-0.16): (0.025-0.3); the molar ratio of nitrogen-containing ligand to metal element M is (0.2-2): 1. Specifically, the water used in step S1 can be water commonly used in the synthesis of molecular sieves, and in order to avoid the introduction of heteroatoms, it is preferably deionized water.
[0093] In a preferred embodiment, step S1 comprises:
[0094] a. mixing a template, a silicon source and water to obtain a silicon hydrolysis solution;
[0095] b. adding a nitrogen-containing ligand to an aqueous solution of a metal M precursor, and mixing the mixture to obtain a first mixed material; and mixing the first mixed material with the hydrolyzed silicon solution to obtain a second mixed material;
[0096] c. Adding a silanization agent to the second mixed material, and mixing to obtain the reaction mixture; preferably, the mixing conditions in step c include: stirring at 20 to 80° C. for 0.5 to 2 hours.
[0097] In one embodiment, in step S1, the silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol; preferably, it is selected from at least one of organic silicone grease, solid silica gel and white carbon black; the general formula of the organic silicone grease is the structure shown in the following formula (A):
[0098]
[0099] Where R a , R b , R c , R d Each is independently selected from an alkyl group having 1 to 6 carbon atoms, wherein the alkyl group is a branched or straight chain alkyl group; preferably, R a , R b , R c , R d Each is independently selected from a straight chain alkyl group having 1 to 4 carbon atoms or a branched chain alkyl group having 3 to 4 carbon atoms. a , R b , R c , R d Each is independently methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl. a , R b , R c , R d Each is independently methyl or ethyl.
[0100] In a preferred embodiment, the organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicone grease.
[0101] According to the present disclosure, in step S1, the template is an organic base, preferably at least one selected from quaternary ammonium base, aliphatic amine and aliphatic alcohol amine. The quaternary ammonium base may be an organic quaternary ammonium base; the aliphatic amine may be a compound formed by replacing at least one hydrogen in NH3 with an aliphatic hydrocarbon group (such as an alkyl group); the aliphatic alcohol amine may be a compound formed by replacing at least one hydrogen in various NH3 with an aliphatic group (such as an alkyl group) containing a hydroxyl group.
[0102] Further preferably, the template is selected from at least one quaternary ammonium base having a structure represented by the following formula (B):
[0103] R1, R2, R3 and R4 are independently selected from alkyl groups having 1 to 4 carbon atoms, preferably straight-chain alkyl groups having 1 to 4 carbon atoms and branched-chain alkyl groups having 3 to 4 carbon atoms, more preferably R1, R2, R3 and R4 are independently selected from at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.
[0104] The template agent is preferably at least one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide (including various isomers of tetrapropylammonium hydroxide, such as tetra-n-propylammonium hydroxide and tetraisopropylammonium hydroxide) and tetrabutylammonium hydroxide (including various isomers of tetrabutylammonium hydroxide, such as tetra-n-butylammonium hydroxide and tetraisobutylammonium hydroxide).
[0105] In a preferred embodiment, the molecular sieve of the composite material is an MFI type molecular sieve, and the template is tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide; or
[0106] The molecular sieve of the composite material is a MEL type molecular sieve, and the template agent is tetrabutylammonium hydroxide or a mixture of tetrabutylammonium hydroxide and one or more selected from tetrabutylammonium chloride and tetrabutylammonium bromide; or
[0107] The molecular sieve of the composite material is a BEA type molecular sieve, and the template agent is tetraethylammonium hydroxide or a mixture of tetraethylammonium hydroxide and one or more selected from tetraethylammonium chloride and tetraethylammonium bromide. The present disclosure can prepare molecular sieves with different structures by selecting different template agents.
[0108] In one embodiment, in step a, the silicon source is organic silicone grease, and after the template, the organic silicone grease and water are mixed, a hydrolysis and alcohol removal treatment is further performed to obtain a hydrolyzed solution of the silicon;
[0109] The conditions for the hydrolysis and alcohol removal treatment include: stirring and hydrolyzing at 0 to 95° C. for 2 to 10 hours; preferably stirring and hydrolyzing at 50 to 95° C. for 2 to 8 hours.
[0110] Preferably, the hydrolysis-alcohol removal treatment is performed so that the mass content of alcohol produced by hydrolysis of the obtained organic silicone grease in the hydrolysis solution of silicon is less than 10 ppm.
[0111] According to the present disclosure, the optional range of types of the metal precursor is relatively wide, and any substance containing the metal (such as a compound containing a metal element and / or a metal single substance) can achieve the purpose of the present disclosure.
[0112] In one embodiment, in step S1, the metal M precursor is one or more of an inorganic metal compound and an organic metal compound; the organic metal compound is a water-soluble inorganic salt of metal M; the water-soluble inorganic salt of metal M is selected from one or more of chloride, hydrated chloride, sulfate, hydrated sulfate and nitrate of metal M; the organic metal compound is an organic ligand compound of metal M; preferably, the metal M precursor is a water-soluble inorganic salt of metal M;
[0113] The metal M is selected from one or more of manganese, iron, cobalt, nickel, palladium, platinum, copper and gold;
[0114] Preferably, the metal M precursor is an aqueous solution of a metal M precursor, and the molar ratio of the metal M element to water in the aqueous solution of the metal M precursor is 1:(50-500).
[0115] In one embodiment, in step S1, the general formula of the silanization agent is R5Si(R6)(R7)R8, wherein R5, R6, R7, and R8 are each independently a halogen, an alkyl group, an alkoxy group, an aromatic group, a thiol group, or an amine group, and at least one of R5, R6, R7, and R8 is an alkyl group, an alkoxy group, an aromatic group, a thiol group, or an amine group; the number of carbon atoms of the alkyl group, the alkoxy group, the thiol group, and the amine group is each independently 1 to 18, preferably 1 to 12; the number of carbon atoms of the aromatic group can be 6 to 18, preferably 6 to 12;
[0116] Preferably, the silanization agent is selected from one or more of dimethyldichlorosilane, N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, 1,7-dichlorooctylmethyltetrasiloxane, hexadecyltrimethoxysilane, octyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane; further preferably, it is at least one of N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane.
[0117] In one embodiment, in step S1, the nitrogen-containing ligand is an alkylamine compound containing only amino groups or an amine compound containing other coordination groups, and the other coordination groups include one or more of hydroxyl, carboxyl, carbonyl, and thiol. In the present disclosure, the "alkylamine compound containing only amino groups" means that the alkylamine compound contains only amino groups, which is a nitrogen-containing group, and does not contain other types of nitrogen-containing groups, but the number of amino groups contained can be one or more.
[0118] Preferably, the nitrogen-containing ligand is one or more of an alkylamine compound containing only an amino group having a structure shown in the following formula (C), an alcoholamine compound having a structure shown in the following formula (D), and an aminocarboxylic acid compound having a structure shown in the following formula (E):
[0119] R9(NH2) n Formula (C); wherein n is 1 or 2; when n is 1, R9 is an alkyl group having 1 to 6 carbon atoms, preferably a linear alkyl group having 1 to 6 carbon atoms and a branched alkyl group having 3 to 6 carbon atoms, and more preferably one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, isopentyl, tert-pentyl and n-hexyl; when n is 2, R9 is an alkylene group having 1 to 6 carbon atoms, preferably a linear alkylene group having 1 to 6 carbon atoms and a branched alkylene group having 3 to 6 carbon atoms, and more preferably one of methylene, ethylene, n-propylene, n-butylene, n-pentylene and n-hexylene;
[0120] (HOR 10 ) m NH (3m) Formula (D); wherein R 10 is an alkylene group having 1 to 4 carbon atoms and a branched alkylene group having 3 to 4 carbon atoms, preferably one of methylene, ethylene, n-propylene and n-butylene; m is 1, 2 or 3. When m is greater than 1, multiple R 10 Same or different;
[0121] (HOOCR 11 ) x NH (3x) Formula (E); wherein R 11 is an alkylene group having 1 to 4 carbon atoms and a branched alkylene group having 3 to 4 carbon atoms, preferably one of methylene, ethylene, n-propylene and n-butylene; x is 1, 2 or 3. When x is greater than 1, multiple R 11 Same or different;
[0122] More preferably, the nitrogen-containing ligand is selected from one or more of ethylamine, ethylenediamine, ethanolamine and ethylenediaminetetraacetic acid.
[0123] In one embodiment, in step S2, the conditions of the hydrothermal crystallization treatment include: under autogenous pressure conditions, the hydrothermal crystallization time is 0.5 to 10 days, and the hydrothermal crystallization temperature is 110 to 200°C; preferably, the hydrothermal crystallization time is 0.5 to 5 days, and the hydrothermal crystallization temperature is 150 to 200°C.
[0124] In one embodiment, in step S2, the conditions of the calcination treatment include: a calcination temperature of 400-900° C., and a calcination time of 1-16 hours; preferably, the calcination temperature is 400-800° C., and the calcination time is 2-8 hours.
[0125] In the present disclosure, the X-ray diffraction (XRD) crystal phase diagram of the sample is measured on a Siemens D5005 X-ray diffractometer, the radiation source is Kα (Cu), and the test range 2θ is 0.5° to 70°.
[0126] The SEM images of the samples were obtained on a Hitachi S4800 high-resolution cold field emission scanning electron microscope.
[0127] The average particle size of the metal oxide nanoparticles was obtained based on TEM measurements.
[0128] The Fourier transform infrared (FT-IR) spectra of the samples were measured on a Nicolet 8210 Fourier transform infrared spectrometer in the range of 400 to 4000 cm -1 .
[0129] The total specific surface area and total pore volume of the samples were measured using a Micromeritics ASAP245 static nitrogen adsorption instrument according to ASTM D4222-98 standard method.
[0130] The present disclosure is further described in detail below through examples.
[0131] Preparation Example 1
[0132] (1) 1.6 g of a 25.05 wt % tetrapropylammonium hydroxide (TPAOH) aqueous solution, 20.8 g of tetraethyl silicate and 52.8 g of water were added to a 500 mL beaker in sequence, and the mixture was placed on a magnetic stirrer with heating and stirring functions to mix evenly, and stirred at 50° C. for 2 hours, and the evaporated water was replenished regularly to obtain a colorless and transparent silica gel solution;
[0133] (2) 0.03 g of cobalt nitrate hexahydrate and 0.18 g of water were stirred evenly, 0.05 mmol of ethylenediamine was added, and the aqueous solution of cobalt was mixed with the hydrolyzed solution of silicon obtained in step (1);
[0134] (3) adding 0.64 g of N-phenyl-3-aminopropyltrimethoxysilane (PHAPTMS) to the mixture of step (2) and stirring for 0.5 hour;
[0135] (4) transferring the mixture obtained in step (3) into a stainless steel closed reactor, crystallizing at a constant temperature of 175° C. for 24 h to obtain a sample, filtering and washing the obtained sample, drying it at 110° C. for 6 h, and then calcining it in a muffle furnace at 550° C. for 6 h to obtain a metal nanoparticle and molecular sieve composite material product, which is recorded as CAT-1;
[0136] The average particle size, BET surface area, total pore volume, micropore volume and mesopore volume of CAT-1 are shown in Table 2. The FTIR image of CAT-1 is shown in Figure 1 As shown; in the infrared spectrum of this sample, 960cm -1 The peak intensity of the highest peak at 800 cm (absorbance 12%) is -1 The ratio I0 of the peak intensity of the highest peak (absorbance is 15%) is 0.80. The XRD spectrum of CAT-1 is shown in Figure 2 As shown in Figure 2, XRD analysis shows that it has an MFI structure; the SEM image of CAT-1 is shown in Figure 2. Figure 3 As shown. Figure 1 Medium 960cm -1 The characteristic peaks nearby indicate that Co is bound to the surface of the silicon skeleton; Figure 3 It can be seen that the product prepared in this example has a regular shape and uniform size, and the molecular sieve as a whole can reach the nanometer scale, so the metal oxide particles therein are also nanometer scale.
[0137] Preparation Examples 2 to 9
[0138] The corresponding products CAT-2 to CAT-9 were prepared according to the method of Example 1. The ratios, synthesis conditions and results are shown in Table 1. Other conditions and operations are referred to Example 1. The FT-IR images of the products are similar to those of Example 1. Figure 1 Similar; XRD analysis shows that it has MFI structure, and the XRD spectrum is similar to Figure 2 Similar; its SEM image is Figure 3 similar.
[0139] Preparation Example 10
[0140] The cobalt-containing multi-level porous β molecular sieve was prepared by referring to the method of Preparation Example 1, changing the ratio and template agent, and using tetraethylammonium hydroxide (TEAOH) as the template agent. The obtained product was recorded as CAT-10. The ratio, synthesis conditions and results are shown in Table 1.
[0141] Preparation Example 11
[0142] The cobalt-containing multi-level porous MEL molecular sieve was prepared by referring to the method of Example 1, changing the ratio and template agent, and using tetrabutylammonium hydroxide (TBAOH) as the template agent. The obtained product was recorded as CAT-11. The ratio, synthesis conditions and results are shown in Table 1.
[0143] Preparation Example 12
[0144] The corresponding product was prepared according to the method of Example 1, and its proportion, synthesis conditions and results are listed in Table 1. Other conditions and operations were similar to those of Example 1, and the obtained product was recorded as CAT-12. Among them, the hydrothermal crystallization temperature was 120°C, the time was 8 days, the calcination temperature was 850°C, and the calcination time was 10 hours.
[0145] Preparation Comparative Example 1
[0146] The product was prepared according to the method of Preparation Example 1, except that no silanization agent was added. The obtained product was recorded as DCAT-1.
[0147] Preparation Comparative Example 2
[0148] 0.03 g of cobalt nitrate hexahydrate and 0.18 g of water were stirred evenly to obtain a cobalt aqueous solution, and then 10.2 g of an alumina carrier was added. The mixture was stirred for 4 h and evaporated to dryness. The solid was collected and dried at 110 °C for 6 h, and then calcined at 550 °C in a muffle furnace for 6 h. The obtained product was recorded as DCAT-2.
[0149] Preparation Comparative Example 3
[0150] 0.03g of cobalt nitrate hexahydrate and 0.18g of water were stirred evenly to obtain a cobalt aqueous solution, and then 6g of all-silicon MFI molecular sieve carrier was added, stirred for 4h, evaporated to dryness, and the solid was collected and dried at 110°C for 6 hours, and then calcined at 550°C in a muffle furnace for 6 hours. The obtained product was recorded as DCAT-3. The preparation process of all-silicon MFI molecular sieve is shown in Preparation Example 1, which is different from Preparation Example 1 in that cobalt nitrate hexahydrate and ethylenediamine are not introduced in the molecular sieve synthesis process, and the rest of the process is the same as Preparation Example 1.
[0151] The average particle size, BET specific surface area, total pore volume, micropore volume and mesopore volume of the products obtained in the above examples and comparative examples are listed in Table 2 below.
[0152] Table 1
[0153]
[0154] In Table 1, TPAOH is tetrapropylammonium hydroxide, TPABr is tetrapropylammonium bromide, TBAOH is tetrabutylammonium hydroxide, TEAOH is tetraethylammonium hydroxide; PHAPTMS is N-phenyl-3-aminopropyltrimethoxysilane, APTES is 3-aminopropyltriethoxysilane, KH792 is silane coupling agent kh792 (bisamino functional group silane); P123 is PEO-PPO-PEO triblock copolymer, CTAB is hexadecyltrimethylammonium bromide, and SDBS is sodium dodecylbenzene sulfonate. The reagents used in the present disclosure can be obtained through conventional purchasing channels.
[0155] Table 2
[0156]
[0157]
[0158] Among them, pores with a diameter less than 2nm are micropores, and pores with a diameter between 2 and 50nm are mesopores.
[0159] According to Table 2, compared with Comparative Example 1 (without adding silanization agent), the products obtained by adding silanization agent during the preparation process of Examples 1 to 12 of the present disclosure have higher mesopore volume, indicating that the method provided by the present disclosure can effectively expand the pores of the molecular sieve.
[0160] Reaction Example 1
[0161] It is used to illustrate the reaction effect of preparing lactone by oxidation reaction provided by the present invention.
[0162] The samples prepared in the above preparation examples and comparative examples were used as catalysts for BV oxidation reactions. 1 mmol of ketone (specific substances are shown in Table 3) was mixed with 0.1 mmol of isobutyraldehyde and 1 mmol of isobutanol, and then contacted with 50 mg of the catalyst in a slurry bed reactor. The contact temperature was 80°C, the contact time was 24 h, and the oxygen pressure was 0.1 MPa. The results are shown in Table 3 below.
[0163] Ketone conversion rate (%) and lactone selectivity (%) were calculated according to the following formula:
[0164] Ketone conversion rate (%) = number of moles of ketone involved in the reaction / number of moles of ketone added × 100%;
[0165] Lactone selectivity (%) = mole number of lactone / mole number of lactone participating in the reaction × 100%;
[0166] The number of moles of ketone participating in the reaction = the number of moles of ketone fed - the number of moles of ketone remaining in the obtained reaction mixture.
[0167] Table 3
[0168]
[0169] According to the data in Table 3, compared with Comparative Examples 1-3, the metal oxide nanoparticles and molecular sieve composite materials I0 prepared in Examples 1 to 12 of the present disclosure are in the range of 0.5 to 1.3, and the composite materials have higher catalytic activity and are used for BV oxidation reactions. Under relatively mild reaction conditions (80°C), more than 80% ketone conversion rate and more than 80% lactone selectivity can be obtained in 24 hours.
[0170] Comparing Examples 1 to 11 with Example 12, the composite catalytic materials I0 prepared in Examples 1 to 11 are in the range of 0.6 to 1.3, and Examples 1 to 11 have better catalytic effects, and have higher ketone conversion rates and lactone selectivities.
[0171] Reaction Example 2
[0172] To illustrate the reaction effect under different reaction conditions, CAT-4 was selected as the catalyst, cyclohexanone was used as the ketone raw material, and the catalyst dosage was 50 mg.
[0173] Referring to the operation process of Reaction Example 1, the reaction conditions were changed. The specific reaction conditions and reaction results are shown in Table 4 below.
[0174] Table 4
[0175]
[0176] According to Tables 3 and 4, by comparing the catalytic effects obtained by using CAT-4 in Reaction Example 2 and Reaction Example 1, it can be seen that when the reaction temperature in Reaction Example 1 is in the range of 80-100° C., the oxidation reaction effect is better, and the ketone conversion rate and lactone selectivity are higher.
[0177] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0178] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0179] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing lactone by oxidation, characterized in that: The method comprises the following steps: Under oxygen conditions, a mixed raw material containing ketone compounds, aldehyde compounds and alcohol compounds is contacted with a catalyst for oxidation reaction; the ketone compound is selected from one or more of aliphatic ketone compounds with carbon atoms of 4 to 10, aromatic ketone compounds with carbon atoms of 8 to 16 and cycloalkanones with carbon atoms of 5 to 10; the aldehyde compound is selected from one or more of isobutylaldehyde, isovaleraldehyde and n-hexanal; the alcohol compound is selected from at least one of primary alcohols and secondary alcohols with carbon atoms of 4 to 10; the reaction temperature of the oxidation reaction is 80-100°C; the weight ratio of the catalyst to the ketone compound is 1:(1-20); The catalyst is a composite material, which includes an all-silicon molecular sieve and a metal element M dispersed in the crystal of the all-silicon molecular sieve, wherein the metal M is selected from one or more of manganese, iron, cobalt and copper; and the metal element M exists in the form of metal nanoparticles; The composite material has the following FT-IR characteristics: The FT-IR spectrum of the composite material has a wave number of 960 cm -1 The peak intensity is recorded as I1, and the wave number is 800 cm -1 The peak intensity is recorded as I2, I0 defined by the following formula (1) is any value between 0.6 and 1.3; I0= I1 / I2 (1); In the composite material, the molar ratio of the metal element M to the silicon element is (0.001-0.2):1; the BET specific surface area of the composite material is 400-800m 2 / g, the total pore volume is 0.3~0.65mL / g, the micropore volume is 0.1~0.19mL / g, the mesopore volume is 0.2~0.46mL / g, and the average particle size of the metal nanoparticles is 0.5~9nm; The catalyst is prepared by a preparation method comprising the following steps: S1, mixing a template, a silicon source, water, a metal M precursor, a nitrogen-containing ligand and a silanization agent to obtain a reaction mixture; S2, subjecting the reaction mixture to hydrothermal crystallization and calcination treatment; The silanization agent is selected from one or more of dimethyldichlorosilane, N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, hexadecyltrimethoxysilane, octyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane; The nitrogen-containing ligand is an alkylamine compound containing only an amino group or an amine compound containing other coordination groups, and the other coordination groups include one or more of hydroxyl, carboxyl, carbonyl, and thiol.
2. The method according to claim 1, characterized in that The molar ratio of the ketone compound, the aldehyde compound and the alcohol compound is 1:(0.05-1):(0.5-5).
3. The method according to claim 2, characterized in that The molar ratio of the ketone compound, the aldehyde compound and the alcohol compound is 1:(0.05-0.5):(0.5-2).
4. The method according to claim 1, characterized in that: The conditions of the oxidation reaction include: reaction time of 1-48h; oxygen pressure of 0.1-0.5MPa.
5. The method according to claim 4, characterized in that The conditions of the oxidation reaction include: reaction time of 2 to 24 hours; oxygen pressure of 0.1 to 0.3 MPa; The weight ratio of the catalyst to the ketone compound is 1:(1-10).
6. The method according to claim 1, characterized in that The reactor for the oxidation reaction includes any one of a tank reactor, a fixed bed reactor, a moving bed reactor, a suspended bed reactor and a slurry bed reactor.
7. The method according to claim 1, characterized in that The all-silicon molecular sieve in the composite material is at least one of an MFI structure molecular sieve, a MEL structure molecular sieve, a BEA structure molecular sieve, an MWW structure molecular sieve, a two-dimensional hexagonal structure molecular sieve, a MOR structure molecular sieve and a TUN structure molecular sieve.
8. The method according to claim 7, characterized in that The all-silicon molecular sieve in the composite material is one or more of a MFI structure molecular sieve, a MEL structure molecular sieve, a BEA structure molecular sieve, a MCM structure molecular sieve and a SBA structure molecular sieve.
9. The method according to claim 8, characterized in that The all-silicon molecular sieve in the composite material is selected from one or more of MFI structure molecular sieve, MEL structure molecular sieve and BEA structure molecular sieve.
10. The method according to claim 1, characterized in that In the composite material, the molar ratio of the metal element M to the silicon element is (0.001-0.16):
1.
11. The method according to claim 1, characterized in that: In step S1, the molar ratio of silicon source: template: water: metal M element: silanization agent calculated as SiO2 is 1: (0.001~1): (5~100): (0.001~0.2): (0.025~0.4); the molar ratio of nitrogen-containing ligand to metal element M is (0.2~2):
1.
12. The method according to claim 11, characterized in that In step S1, the molar ratio of silicon source: template: water: metal M element: silanization agent calculated as SiO2 is 1: (0.001~1): (5~100): (0.001~0.16): (0.025~0.3).
13. The method according to claim 1, characterized in that Step S1 includes: a. mixing a template, a silicon source and water to obtain a silicon hydrolysis solution; b. adding a nitrogen-containing ligand to an aqueous solution of a metal M precursor, and mixing the mixture to obtain a first mixed material; and mixing the first mixed material with the hydrolyzed silicon solution to obtain a second mixed material; c. Adding a silanization agent into the second mixed material and mixing them to obtain the reaction mixture.
14. The method according to claim 13, characterized in that The mixing conditions in step c include: stirring at 20-80° C. for 0.5-2 hours.
15. The method according to claim 1, characterized in that The silicon source is selected from at least one of organic silicone grease, solid silica gel, white carbon black and silica sol.
16. The method according to claim 15, characterized in that The silicon source is selected from at least one of organic silicone grease, solid silica gel and white carbon black.
17. The method according to claim 16, characterized in that The silicon source is organic silicone grease, and the general formula of the organic silicone grease is the structure shown in the following formula (A): (A); Where R a , R b , R c , R d Each is independently selected from an alkyl group having 1 to 6 carbon atoms, and the alkyl group is a branched or straight chain alkyl group.
18. The method according to claim 17, characterized in that In formula (A), R a , R b , R c , R d Each is independently selected from a straight-chain alkyl group having 1 to 4 carbon atoms or a branched-chain alkyl group having 3 to 4 carbon atoms.
19. The method according to claim 17, characterized in that In formula (A), R a , R b , R c , R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl or tert-butyl.
20. The method according to claim 17, characterized in that The organic silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate and dimethyl diethyl silicone grease.
21. The method according to claim 1, characterized in that In step S1, the template agent is an organic base.
22. The method according to claim 1, characterized in that In step S1, the template agent is selected from at least one of quaternary ammonium base, aliphatic amine and aliphatic alcohol amine.
23. The method according to claim 22, characterized in that The template is selected from at least one quaternary ammonium base having a structure represented by the following formula (B): (B); R1, R2, R3 and R4 are independently selected from an alkyl group having 1 to 4 carbon atoms.
24. The method according to claim 23, characterized in that In formula (B), R1, R2, R3 and R4 are independently selected from a linear alkyl group having 1 to 4 carbon atoms and a branched alkyl group having 3 to 4 carbon atoms.
25. The method according to claim 24, characterized in that In formula (B), R1, R2, R3 and R4 are independently selected from at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.
26. The method according to claim 1, characterized in that The molecular sieve of the composite material is an MFI type molecular sieve, and the template agent is tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide; or The molecular sieve of the composite material is a MEL type molecular sieve, and the template agent is tetrabutylammonium hydroxide or a mixture of tetrabutylammonium hydroxide and one or more selected from tetrabutylammonium chloride and tetrabutylammonium bromide; or The molecular sieve of the composite material is a BEA type molecular sieve, and the template agent is tetraethylammonium hydroxide or a mixture of tetraethylammonium hydroxide and one or more selected from tetraethylammonium chloride and tetraethylammonium bromide.
27. The method according to claim 13, characterized in that In step a, the silicon source is organic silicone grease, and after the template, the organic silicone grease and water are mixed, a hydrolysis and alcohol removal treatment is also performed to obtain a hydrolyzed solution of the silicon; The conditions of the hydrolysis and alcohol removal treatment include: stirring and hydrolyzing at 0-95° C. for 2-10 hours.
28. The method according to claim 27, characterized in that The conditions of the hydrolysis and alcohol removal treatment include: stirring and hydrolyzing at 50-95° C. for 2-8 hours.
29. The method according to claim 1, characterized in that In step S1, the metal M precursor is one or more of an inorganic metal compound and an organic metal compound; the inorganic metal compound is a water-soluble inorganic salt of metal M; the water-soluble inorganic salt of metal M is selected from one or more of the chloride, hydrated chloride, sulfate, hydrated sulfate and nitrate of metal M; the organic metal compound is an organic ligand compound of metal M.
30. The method according to claim 29, characterized in that The metal M precursor is a water-soluble inorganic salt of metal M.
31. The method according to claim 13, characterized in that The molar ratio of the metal M element to water in the aqueous solution of the metal M precursor is 1:(50-500).
32. The method according to claim 1, characterized in that The silanization agent is selected from at least one of N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane.
33. The method according to claim 1, characterized in that In step S1, the nitrogen-containing ligand is one or more of an alkylamine compound containing only amino groups having a structure shown in the following formula (C), ethanolamine and ethylenediaminetetraacetic acid; R9(NH2) n Formula (C); Wherein, n is 1 or 2; when n is 1, R9 is an alkyl group having 1 to 6 carbon atoms; when n is 2, R9 is an alkylene group having 1 to 6 carbon atoms.
34. The method according to claim 33, characterized in that In formula (C), when n is 1, R9 is a straight-chain alkyl group having 1 to 6 carbon atoms and a branched-chain alkyl group having 3 to 6 carbon atoms; when n is 2, R9 is a straight-chain alkylene group having 1 to 6 carbon atoms and a branched-chain alkylene group having 3 to 6 carbon atoms.
35. The method according to claim 33, characterized in that In formula (C), when n is 1, R9 is one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, isopentyl, tert-pentyl and n-hexyl; when n is 2, R9 is one of methylene, ethylene, n-propylene, n-butylene, n-pentylene and n-hexylene.
36. The method according to claim 1, characterized in that In step S2, the conditions of the hydrothermal crystallization treatment include: under autogenous pressure conditions, the hydrothermal crystallization time is 0.5 to 10 days, and the hydrothermal crystallization temperature is 110 to 200° C.; The conditions of the calcination treatment include: a calcination temperature of 400-900° C. and a calcination time of 1-16 hours.
37. The method according to claim 36, characterized in that In step S2, the conditions of the hydrothermal crystallization treatment include: the hydrothermal crystallization time is 0.5 to 5 days, and the hydrothermal crystallization temperature is 150 to 200° C.; The conditions of the calcination treatment include: a calcination temperature of 400-800° C. and a calcination time of 2-8 hours.
Citation Information
Patent Citations
Co load MFI molecular sieve with hexagonal prism shape and preparation method thereof
CN102671695A
Method for preparing organic lactone
CN102702152A